Dinâmica cósmica a partir do Diagrama de Hubble de Supernovas Ia e Quasares. - Silveira, Syrios Gomes da (2021)
We revisited a model-independent cosmic acceleration estimator based on the distance modulus presented in (SEIKEL; SCHWARZ, 2008) and initially apply it to type Ia supernova data and mock catalogs to test the coherence with the other methods. Then we upda